TRANSFORMATIONAL LEADERSHIP AS A PREREQUISITE FOR ORGANIZATIONAL INNOVATIONS DURING TURBULENT SOCIO-ECONOMIC CIRCUMSTANCES - Stevanovic, Ana (International Journal of Economic Practice and Policy, 2015)
Currently, many organizations are operating in turbulent socio-economic circumstances which do not represent a matter of certain time, but the only certainty and consistency. There is a necessity for an adequate organizational response to changes so that organizations can remain competitive. The paper highlights the importance of new forms of management and leadership in managing organizations. Transformational leadership represents a form of leadership that encourages and nurtures employee creativity at all levels within the organization - individual, group and organizational, which implies the generating and establishment of organizational innovation. Due to the fact that creativity is a necessary condition for organizational innovation, this paper points out that transformational leadership is essential for the induction of organizational innovations and their management which further results in organizational changes that contribute to the survival and competitiveness of organizations and business systems on the market.